PENGARUH PROMOSI DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING: Studi Kasus Pada J.Co Donuts & Coffee Tebing Tinggi - Ramadina, Diva; Shafira Awaliyah; Dedy Dwi Arseto; Fonaha Hulu (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to determine the Influence of Promotion and Brand Image on Purchase Decisions with Buying Interest as an Intervening Variable in Consumers J.Co Donuts & Coffee Tebing Tinggi. The research method used is a quantitative method using Smart PLS version 3.0. The questionnaire was distributed to 96 respondents. The data analysis methods used in the study are measurement models (outer models), namely validity tests, reliability tests, then structural models (inner models) including: determination coefficient/r-square (r2) and hypothesis testing with t-statistical tests and indirect influence tests. The results of Smart PLS 3.0 in this study are that Promotion affects Buying Interest in J.Co Donuts & Coffee, Brand Image affects Buying Interest in J.Co Donuts & Coffee, Promotion has no effect on Purchase Decision at J.Co Donuts & Coffee, Brand Image affects Purchase Decision at J.Co Donuts & Coffee, Buying Interest affects Purchase Decision at J.Co Donuts & Coffee, Promotion affects Purchase Decisions with Buying Interest as an Intervening Variable in J.Co Donuts & Coffee, Brand Image affects Purchase Decisions with Buying Interest as an Intervening Variable in J.Co Donuts & Coffee.